Impact of pre-transplant pulmonary infection developed in horizontal laminar flow unit on the outcome of subsequent allogeneic hematopoietic stem cell transplantation - He, Gan-Lin; Chang, Ying-Jun; Xu, Lan-Ping; Zhang, Xiao-Hui; Wang, Yu; Liu, Kai-Yan; Huang, Xiao-Jun (Journal of Thoracic Disease, 2016)
Background: So far, there is very little literature on how pre-transplant pulmonary infection developed in horizontal laminar flow unit (HLFU) affects outcomes of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods: A retrospective analysis was performed on allo-HSCT recipients who were diagnosed with pre-transplant pulmonary infection developed in HLFU between January 2012 and December 2012. Various tests were analyzed to evaluate the overall survival (OS) and pulmonary infection rate after allo-HSCT. Results: Among 317 patients who received allo-HSCT from related donors, 7 cases of human leukocyte antigen (HLA)-haploidentical transplantation reported a fever, cough, and other symptoms before transplantation. Chest radiography findings showed pulmonary infection, and the C-reactive protein (CRP) level was higher than normal, which confirmed pulmonary infection (incidence rate 2.21%). The Breslow test suggested that the early survival rate was lower in the group with pre-transplant pulmonary infection than in the group without pre-transplant pulmonary infection (OS: 28.4 vs. 42.4 months; P=0.023); the early survival rate was lower in patients with a pulmonary infection accompanied by bilateral pleural effusion than in patients without pleural effusion (OS: 1.5 vs. 36.3 months; P=0.010). In the first month after transplantation, the difference in the CD4CD45RO+CD45RA- and CD4CD45RO-CD45RA+ between the groups with and without pre-transplant pulmonary infection was statistically significant (P3 years had a higher rate of pulmonary infection in the first 2 months after allo-HSCT than those without pre-transplant pulmonary infection [100% (5/5 patients) vs. 38.1% (118/310); χ2=5.542, P=0.019]. Conclusions: Development of pre-transplant pulmonary infection in the HLFU in patients with hematological malignancies who receive HLA-haploidentical HSCT is associated with an increased risk of recurrent pulmonary infection in the early period after transplantation; however, there is no impact on patients’ long-term survival rate.